Modified integral sliding mode speed controller for predictive stator flux and torque controlled induction motor drive - Hau Huu Vo; Dat Vinh Phat Tran (Institute of Advanced Engineering and Science, 2026)
The paper deals with utilization of integral sliding mode (SM) in speed controller of predictive torque and flux control (PTC) of induction motor (IM). At first, the model-based prediction of the motor torque and stator flux is presented. Then, the voltage vector of the inverter is selected to minimize the errors of the torque and the flux. The proportional-integral (PI) speed controller is used to provide the reference torque for the torque controller. However, the PI speed controller is not achieved high performance especially in cases of high load torque and low speed commands. Then, the integral SM one is employed to enhance the speed control performance. Simulations of two speed controllers in PTC drive are carried out. Evaluations using criterions relevant to speed error confirm the expected performance of the integral SM speed controller.